High-Accuracy PVT Relationships for Compressed Fluids and Their Application to BET-like Modelling of CO and CH Adsorption - Janina Milewska-Duda; Jan Tadeusz Duda (Adsorption Science & Technology)
This paper presents a set of high-accuracy formulae enabling the evaluation of the compression factor, activity and cohesion energy of fluids at near-critical and super-critical temperatures, with reduced molar volumes ranging from 0.4. Such data are necessary in BET-like theoretical modelling of adsorption process. The proposed fluid state equation (PVT relationship) combines a theoretical description of the fluid entropy (based on a hard-sphere model) with cohesion energy relationships obtained via high-accuracy approximations of universal compression factor data and vapour-liquid equilibria. The resultant relationships are incorporated into a BET-like description of adsorption in materials of irregular microporous structure (LBET model). The set of formulae gathered together in this paper allows the possible effective calculation of adsorption isotherms at near- and super-critical temperatures relative to the pore structures. A multi-variant fitting of the LBET model to the empirical data is proposed to detect active constraints for multilayer adsorption and, hence, to obtain information on the structure of the pores. Application of the formulae to the analysis of methane and carbon dioxide adsorption onto an active carbon is discussed.